A systematic review of management strategies for children's mental health care in the emergency department: update on evidence and recommendations for clinical practice and research. Issue 6 (24th January 2017) - Newton, Amanda S; Hartling, Lisa; Soleimani, Amir; Kirkland, Scott; Dyson, Michele P; Cappelli, Mario
Abstract : Objective: Children with mental health crises require access to specialised resources and services which are not yet standard in general and paediatric EDs. In 2010, we published a systematic review that provided some evidence to support the use of specialised care models to reduce hospitalisation, return ED visits and length of ED stay. We perform a systematic review to update the evidence base and inform current policy statements. Methods: Twelve databases and the grey literature were searched up to January 2015. Seven studies were included in the review (four newly identified studies). These studies compared ED-based strategies designed to assess, treat and/or therapeutically support or manage a mental health presentation. The methodological quality of six studies was assessed using the Cochrane Effective Practice and Organization of Care Risk of Bias tool (one interrupted time series study) and a modified Newcastle-Ottawa Scale (three retrospective cohort and two before–after studies). The Grading of Recommendations Assessment, Development and Evaluation (GRADE) system was applied to rate overall evidence quality (high, moderate, low or very low) for individual outcomes from these six studies. An additional study evaluated the psychometric properties of a clinical instrument and was assessed using criteria developed by the Society of Pediatric Psychology Assessment Task Force (well-established, approaching well-established or promising assessment). Results: There is low to very low overall evidence quality that: (1) use of screening laboratory tests to medically clear mental health patients increases length of ED stay and costs, but does not increase the risk of clinical management or disposition change if not conducted; and (2) specialised models of ED care reduce lengths of ED stay, security man-hours and restraint orders. One mental health assessment tool of promising quality, the home, education, activities and peers, drugs and alcohol, suicidality, emotions and behaviour, discharge resources (HEADS-ED), has had good accuracy in predicting admission to inpatient psychiatry. Conclusions: Lower-quality data suggest benefits to the use of specialised resources and services for paediatric mental health care in general and paediatric EDs. Experimental evaluation of strategies and the inclusion of patient-reported outcomes will improve confidence in these findings. Additional psychometric studies are needed for the HEADS-ED tool to be considered well established.